2018
DOI: 10.1016/j.envpol.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A workflow for improving estimates of microplastic contamination in marine waters: A case study from North-Western Australia

Abstract: Plastic pollution is ubiquitous throughout the marine environment, with microplastic (i.e. <5 mm) contamination a global issue of emerging concern. The lack of universally accepted methods for quantifying microplastic contamination, including consistent application of microscopy, photography, an spectroscopy and photography, may result in unrealistic contamination estimates. Here, we present and apply an analysis workflow tailored to quantifying microplastic contamination in marine waters, incorporating stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 67 publications
1
83
0
1
Order By: Relevance
“…Particles with a match of at least 700 (out of 1000) were counted as safely identified. If the match ranged between 600 and 700 the spectra were manually compared to database spectra and evaluated based on expert knowledge, as suggested by other studies (Hanke et al, 2013;Kroon et al, 2018;Lusher et al, 2013).…”
Section: Identification and Quantification Of Mp >500 µM Using Atr-ftirmentioning
confidence: 99%
See 2 more Smart Citations
“…Particles with a match of at least 700 (out of 1000) were counted as safely identified. If the match ranged between 600 and 700 the spectra were manually compared to database spectra and evaluated based on expert knowledge, as suggested by other studies (Hanke et al, 2013;Kroon et al, 2018;Lusher et al, 2013).…”
Section: Identification and Quantification Of Mp >500 µM Using Atr-ftirmentioning
confidence: 99%
“…It has been shown that visual identification alone is insufficient (Kroon et al, 2018;Song et al, 2015) imaging are the most commonly used (Hanke et al, 2013;Käppler et al, 2016;Silva et al, 2018). Generally, there is a requirement within the research field to establish the usage of polymer characterization methods that omit the need for pre-sorting.…”
Section: Interstudy Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of them (14) employed no chemical confirmation to guarantee plastic as the material and relied on visual observation alone. The smaller the particle, the less accurate the plastic identification by visual techniques, with particles below 1.5 mm having a significant increase in error of identification (Löder et al, 2017;Kroon et al, 2018). Raman and FTIR spectroscopy are complimentary techniques for determining microplastic polymer types, as they are able to characterize extremely small microplastics (with a minimum size of 1 µm and 20 µm, respectively) (Käppler et al, 2016).…”
Section: Standardizationmentioning
confidence: 99%
“…Air, water, and soil are continuously being exposed to these intruders and, as a direct consequence, human beings, and all living organisms on the planet as well. One of the most mediatic contaminants during the recent years among the aforementioned are plastics, microplastics, and nanoplastics, being a huge problem in our oceans and river waters (Zhu et al 2018;Alimi et al 2018;Kroon et al 2018).…”
mentioning
confidence: 99%